2000
DOI: 10.1097/00004836-200010000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Gallstone Recurrence After Successful Extracorporeal Shock Wave Lithotripsy

Abstract: Ninety-six patients treated successively for symptomatic cholelithiasis with extracorporeal shock wave lithotripsy (ESWL) and oral bile acid therapy consisting of ursodeoxycholic acid in daily dosages of 600 mg were prospectively followed for gallstone recurrence for a median of 13 months. Ultrasonography was performed to detect stone recurrence at 3, 6, and 12 months, and then yearly after the termination of therapy. Recurrent stones were found in 17 patients (18%). The cumulative probability of gallstone rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Recurrence following ESWL is a problem as the 10-year recurrence rate has been estimated to be 54-60% [90,91], and patients with reduced gallbladder function are likelier to experience recurrence [92]. UDCA has also been reported to be effective for preventing recurrence [86,87].…”
Section: Commentarymentioning
confidence: 99%
“…Recurrence following ESWL is a problem as the 10-year recurrence rate has been estimated to be 54-60% [90,91], and patients with reduced gallbladder function are likelier to experience recurrence [92]. UDCA has also been reported to be effective for preventing recurrence [86,87].…”
Section: Commentarymentioning
confidence: 99%
“…Both Tsumita et al22 and Venneman et al23 give a clue that the probability of stone recurrence is significantly higher in patients with poor gallbladder contractility than in those with good contractility. Ochi et al24 provide a link that the rate of impaired gallbladder contractility was higher in ESWL patients with recurrence when compared with those with no recurrence. Our research gives another link that lithotrity may result in impaired gallbladder contractility, which functions as a bridge between lithotrity and stone recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…These data are similar to those of the postdissolution trial by Tomida et al (18), who reported a cholecystectomy rate of 26%. Differences are partly explained by the patient number included in the respective trials: The smaller the trial size, the smaller the number of patients who were operated on (19)(20)(21). Our rates of CE are similar to the figures reported by Ahmed et al, who caried out a follow-up of patients after ESWL or CE (22).…”
Section: Discussionmentioning
confidence: 99%